The Fruits of the Myrtle Syzygium Cumini, a Botanical, Phytochemical and Emblematic Treasure from the Bible - Robijaona Rahelivololoniaina B (Budapest International Research and Critics University, 2023)
This study on the valorization of Syzygium cumini fruit pulp was carried out in Antananarivo-Madagascar. The aim was to find a substitute for grape wine at Christian feasts. What drew our attention to the jamuns was their resemblance to grapes in bunches during fruiting and their identical color when ripe. Research undertaken through physico-chemical analyses of these fruits and the products derived from their fermentation has led to the conclusion that ordinary chemical families, such as anthocyanins (0.012 mg/g), produce a wine that is similar to grape wine in taste, slightly astringent, and color, however low its alcoholic strength. So, it would be possible to offer this type of wine that would not make anyone drunk.